Construction and validation of an educational game for pregnant women - Carla Gisele D'Avila; Ana Claudia Puggina; Rosa Aurea Quintella Fernandes (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objectives: To design an educational game for the guidance of pregnant women regarding their rights and good practices in the birth process and to validate the content of the textual information and images of the game with the collaboration of judges. Method: This was a methodological, quantitative study. The validation of the content was carried out by 10 judges. Results: Of the 44 cards, only two were questioned and did not achieve 90% agreement, the image of card number 2 (p = 0.01) and the content of card number 9 (p = 0.01). Conclusion: The construction and validation of the content of the game proved to be adequate and feasible for guiding and preparing pregnant women regarding good care practices in the birth process.